Providers' Shift to Telerehabilitation at the U.S. Veterans Health Administration During COVID-19: Practical Applications - Kreider, Consuelo M.; Hale-Gallardo, Jennifer; Kramer, John C.; Mburu, Sharon; Slamka, Mackenzi R.; Findley, Kimberly E.; Myers, Keith J.; Romero, Sergio (Frontiers in Public Health, 2022)
Telerehabilitation provides Veteran patients with necessary rehabilitation treatment, enhancing care continuity and reducing travel time for Veterans who may have to travel long distances to receive rehabilitation care at a Veterans Health Administration (VHA) medical facility. The onset of the COVID-19 pandemic necessitated a sudden shift to telehealth – including telerehabilitation, where there exists a paucity of data-driven guidelines specific to the practicalities entailed in telerehabilitation implementation. This paper explicates gains in practical knowledge for implementing telerehabilitation that were accelerated during the VHA healthcare systems’ rapid shift from out-patient rehabilitation services to telerehabilitation during the COVID 19 pandemic. Group and individual interviews with 12 VHA rehabilitation providers were conducted to examine, in-depth, the providers’ implementation of telerehabilitation. Thematic analysis yielded nine themes: Willingness to Give Telerehabilitation a Chance: A Key Ingredient; Creativity and Adaptability: Critical Attributes for Telerehabilitation Providers; Adapting Assessments; Adapting Interventions; Role and Workflow Adaptations; Appraising for Self the Feasibility of the Telerehabilitation Modality; Availability of Informal, In-Person Support Improves Feasibility of Telerehabilitation; Shifts in the Expectations by the Patients and by the Provider; Benefit and Anticipated Future of Telerehabilitation. This paper contributes in-depth understanding of clinical reasoning considerations, supportive strategies, and practical approaches for engaging Veterans in telerehabilitation.